Uncategorized

Solution: Solve (y – √(x^2 + y^2)) dx – x dy = 0

Solve (y – √(x2 + y2)) dx – x dy = 0

Problem Statement: EE Board April 1995

Solve (y – √(x2 + y2)) dx – x dy = 0

  • A. √(x2 + y2 ) + y = C
  • B. √(x2 + y2 + y) = C
  • C. √(x + y) + y = C
  • D. √(x2 – y) + y = C

Problem Answer:

The solution is √(x2 + y2 ) + y = C

Solution:

Latest Problem Solving in Differential Equations

div.feedburnerFeedBlock ul li {background: #E2F0FD;
list-style-type: none;
margin:0 0 5px 0px;
padding:5px 5px 5px 10px !important;
border: 1px solid #0080ff;
border-radius:8px;
-moz-border-radius:8px;
-webkit-border-radius:8px;

}

div.feedburnerFeedBlock ul li:hover {
background:#ffffff;
}

div.feedburnerFeedBlock ul li a{
color:#ffffff;
text-decoration:none;
}

div.feedburnerFeedBlock ul li a:hover {
text-decoration: underline;
color: #000000;
}
div #creditfooter{
display: none;
}

More Questions in: Differential Equations

Online Questions and Answers in Differential Equations

Leave a Reply

Your email address will not be published. Required fields are marked *